Utilizing a Faculty Development Program to Promote Safer Opioid Prescribing for Chronic Pain in Internal Medicine Resident Practices. Issue 4 (12th January 2019) - Roy, Payel; Jackson, Angela H; Baxter, Jeffrey; Brett, Belle; Winter, Michael; Hardesty, Ilana; Alford, Daniel P
Abstract: Objective: To implement a skills-based faculty development program (FDP) to improve Internal Medicine faculty's clinical skills and resident teaching about safe opioid prescribing. Design: An FDP for Internal Medicine attendings that included a one-hour didactic presentation followed immediately by an Objective Structured Clinical Examination (OSCE) that focused on assessing and managing opioid misuse risk, opioid treatment outcomes (benefits and harms), and aberrant opioid use behaviors. The evaluation compared pre- and three-months-post-FDP changes in faculty's safe opioid prescribing knowledge, attitudes, confidence (clinical and teaching), and self-reported resident teaching. Results: The 25 Internal Medicine faculty participants had a mean of 13 years in clinical practice, including 10 years precepting residents. During the three months post-FDP, faculty treated a mean of 22 patients with chronic pain on long-term opioids and precepted a mean of seven residents caring for patients on long-term opioids. At three months post-FDP, there were significant improvements in correct responses to knowledge questions (68% to 79% P  = 0.008), "high-level" confidence in safer opioid prescribing clinical practice (43.5% to 82.6% P  = 0.007) and resident teaching (45.8% to 83.3%, P  = 0.007), and improvements in alignment of desired attitudes toward safer opioid prescribing. There were nonsignificant increases in self-reported safe opioid prescribing resident teaching. Conclusions: A skills-based faculty development program that includes a lecture followed by an OSCE can improve Internal Medicine faculty safe opioid prescribing knowledge, attitudes, and clinical and teaching confidence. Improving resident teaching may require additional training in safe opioid prescribing teaching skills.